Smart Mobility: Contradictions in Value Co-Creation - Schulz, Thomas; Gewald, Heiko; Böhm, Markus; Krcmar, Helmut (Information systems frontiers, 2023)
Technical progress is disrupting the mobility sector. New door-to-door (D2D) mobility integrators promise to offer smart mobility by packaging together different mobility services such as car-sharing and public transport. However, mobility providers up to now have rarely entered into value co-creation relationships. As a result, citizens are offered mobility that cannot be considered truly smart. Although value co-creation has been the subject of numerous studies taking the service-dominant logic perspective, this research has often lacked empirical evidence. To close this gap, we conceptualize value co-creation between mobility providers and a D2D mobility integrator by applying Activity Theory. Based on a qualitative study in the German mobility sector, we identify several inhibitors of value co-creation from the viewpoint of mobility providers. In addition, we show how these inhibitors serve as triggers for adaptations, ultimately leading to the formation of a value co-creation relationship.